What Matters Most in Life? A German Cohort Study on the Sources of Meaning and Their Neurobiological Foundations in Four Age Groups - Karwetzky, Christopher; Werdecker, Lena; Esch, Tobias (Frontiers in Psychology, 2021)
Existing work in the field of positive psychology suggests that people can draw meaning from a variety of sources. The present study aimed to identify the most important sources of meaning and to explore the role of age and neural adaptation processes in this context. As part of a large German cohort study, 1,586 individuals between 12 and 94 years were asked to provide a maximum of five responses to the question “What matters most to you in life?” We divided the study population into four age groups and analyzed the obtained answers qualitatively and quantitatively using (1) word clouds and (2) frequency comparisons based on a summarizing content analysis. A chi-squared test was used to test the observed differences between age groups. Identified sources of meaning could be clustered into 16 main and 76 subcategories, with relationships (by 90% of respondents) and health and well-being (by 65% of respondents) being the most frequently named main categories, followed by a good living environment (by 28%), (leisure) time (by 26%), and work (by 24%). The study revealed some remarkable age-related patterns. While the importance of partnership increased with age, social networks were less important to older individuals. We also found that, for example, the importance of self-realization, success and career decreased with age, while the opposite was true for life satisfaction and peace and harmony (increasing importance with age). Security was most important to individuals in the two middle age groups between 30 and 69 years. The study advances our understanding of meaning across various ages by showing that individuals of different ages perceive different things as meaningful to them. Interpreting our results in the light of a neurobiological model of motivation systems, we argue that neural adaptation processes may play an important role in the (changing) perceptions of meaning throughout life.